Community-Based Screening of Infertility Risk Factors Among Reproductive-Aged Couples in Bantul, Yogyakarta, Indonesia - Rizqitha; Yofi Kurniawati (Jurnal Riset Daerah, 2026)
Infertility is a growing public health concern with multifactorial determinants affecting both partners, yet early identification of risk factors at the community level remains limited. This study aimed to assess the prevalence and distribution of infertility risk factors among reproductive-aged couples in Bantul, Yogyakarta, Indonesia, using a community-based screening approach. A community-based cross-sectional study was conducted from May to August 2025 involving 48 reproductive-aged couples selected through purposive sampling during community health screening activities. Data were collected using a structured, interviewer-administered questionnaire assessing sociodemographic characteristics, reproductive history, lifestyle factors, and medical conditions related to infertility, combined with anthropometric measurements for body mass index assessment. An infertility risk scoring system was applied to classify participants into low- and elevated-risk groups, and descriptive statistical analysis was performed. Approximately 39.6% of participants were classified as having elevated infertility risk. Key risk factors identified included menstrual irregularities, abnormal body mass index, smoking behavior among male partners, and a history of reproductive health disorders. These findings highlight the importance of early community-based screening to detect modifiable infertility risk factors prior to clinical manifestation. Community-based screening may support early identification and inform preventive reproductive health strategies.